Impacts of Climate Change on the Global Wine Sector: The Case of Cool-Climate Countries - Jeremiás Máté Balogh; Zalán Márk Maró (Amfiteatru Economic, 2025)
Over the last decades, climate change has been playing an increasingly significant role in humanity and has greatly affected world wine-producing regions. There are already remarkable changes in wine production (for example, plantation of new heat-tolerant grape varieties, growing wine grape varieties in cool climates, and expanding vineyards in cool climate regions). The article aims to investigate the effects of climate change (the change in annual average temperature and the variability of precipitation) on the wine sector between 1961 and 2023, focussing on cool climate regions of the world. Descriptive statistics and a panel data analysis are applied to explore the impacts of climate change on the global wine sector (66 countries), considering countries with cool climate (11 countries). Panel econometrics research on climate change effects in cool climate countries is limited, with few studies examining grape and wine production in these regions. Thus, the originality of the research lies in the use of large-sample longitudinal data analysis to examine the impact of climate change on wine production considering cool-climate regions, focussing on an area that has been ignored in previous research. According to the results, an increase in temperature has a negative effect, while an intensification in precipitation has a positive impact on wine production in the examined countries, suggesting that global warming may be balanced by precipitation, especially in drought-prone areas. Furthermore, countries with cool climates are not yet significant players in the global wine industry, but they have great potential for a change in vineyard areas due to climate change and its consequences.